Nataliya D. | Patient and effective tutor for your most difficult subject.Patient and effective tutor for your mos...

0

3x - 2y = 8 Let's multiply this equation by 2 ----> 6x - 4y = 16
2x + 5y = -1 Let's multiply this equation by (-3) -6x - 15y = 3
Now, let's add them up 0 - 19y = 19
y = -1
Next, in first equation, let's substitute y by its value
3x - 2(-1) = 8 ------> 3x + 2 = 8 ----> x = 2
The answer is pair of numbers (2, -1)

## Comments

Hi Amber. Please, help us to serve you better. Copy the problem correctly. Thank you

3x - 2 y = 8 .2x + 5y = -1

they rite under each other

Thank you, Amber, just want to be sure that second equation is "0.2x + 5y = -1" especially underlined coefficient.

Its 2x + 5y = -1